2007
DOI: 10.1124/mol.106.029942
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Modulates the Interaction of the Endogenous Neurosteroid Allopregnanolone with the α1β2γ2L GABAA Receptor

Abstract: We have examined ␣1␤2␥2L GABA A receptor modulation by the endogenous steroids allopregnanolone (3␣5␣P), pregnenolone sulfate, and ␤-estradiol in the absence and presence of ethanol. Coapplication of 0.1 to 1% (17-170 mM) ethanol influenced receptor modulation by 3␣5␣P but not that by pregnenolone sulfate or ␤-estradiol. One of the three kinetic effects evident in channel potentiation by 3␣5␣P, prolongation of the longest-lived open time component (OT3), was affected by ethanol with the midpoint of its dose-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…A recent report highlighted that effect of the neurosteroid allopregnanolone on prolonging the long open-times of single α1β2γ2L GABA A R channels expressed in HEK 293 cells activated by 50 μM GABA was shifted to 100-fold lower neurosteroid concentrations in the presence of 17 mM ethanol (Akk et al, 2007). However, this effect was not evident in the whole-cell currents evoked by GABA, possibly because of the relatively small contribution of the long openings to the total current.…”
Section: Tonic Inhibition As a Common Target For Ethanol And Neurostementioning
confidence: 88%
“…A recent report highlighted that effect of the neurosteroid allopregnanolone on prolonging the long open-times of single α1β2γ2L GABA A R channels expressed in HEK 293 cells activated by 50 μM GABA was shifted to 100-fold lower neurosteroid concentrations in the presence of 17 mM ethanol (Akk et al, 2007). However, this effect was not evident in the whole-cell currents evoked by GABA, possibly because of the relatively small contribution of the long openings to the total current.…”
Section: Tonic Inhibition As a Common Target For Ethanol And Neurostementioning
confidence: 88%
“…A recent study showed a similar interaction between an endogenous neurosteroid, 3α5αP, and ethanol (Akk et al, 2007). Coapplication of the two drugs, at concentrations ineffective individually, resulted in a significant increase in the duration of OT3 without affecting the relative frequency of OT3 or the channel closing rate.…”
Section: D Steroid/ethanol Interactionsmentioning
confidence: 95%
“…First, there is an indirect effect, where the application of ethanol modifies the level of some endogenous GABA A receptor modulator without affecting the ability of the receptor to respond to the stimulus (Barbaccia et al, 1999;Morrow et al, 2001;O'Dell et al, 2004;Sanna et al, 2004;VanDoren et al, 2000). Second is a direct interaction, where exposure to ethanol modifies the ability of the receptor to respond to a stimulus, which otherwise would have been ineffective at modulating receptor function (Akk et al, 2007;Murayama et al, 2006). VanDoren et al (2000) showed that administration of ethanol was followed by an increase in the levels of 3α5αP in the rodent cerebral cortex.…”
Section: D Steroid/ethanol Interactionsmentioning
confidence: 99%
“…These findings have not, however, been replicated in other labs (Borghese and Harris, 2007;Korpi et al, 2007). In addition, it is currently a subject of debate as to whether low concentrations of alcohol affect only α 4 , α 6 and δ subunits (Lovinger and Homanics, 2007), For example, it has been shown that co-application of low concentrations of ethanol (17mM) influences channel potentiation of at least the α 1 β 2 γ 2 receptor by neurosteroids (Akk et al, 2007). Moreover, α 1 δ subunit assemblies that are highly sensitive to low concentrations of ethanol and mediate tonic inhibitory currents have recently been detected in hippocampal interneurons (Glykys et al, 2007).…”
Section: Presynaptic Postsynaptic and Extrasynaptic Receptors: Phasimentioning
confidence: 97%